Preformulation Considerations Development and Evaluation of Mesalamine Loaded Polysaccharide-Based Complex Mucoadhesive Beads for Colon Targeting - Deshmukh, Rohitas; Harwansh, Ranjit Kumar (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Inflammatory bowel disease (IBD) is a chronic inflammatory disease of large intestine consisting of ulcerative colitis and Crohn’s disease. Mesalamine is a first line drug use for the treatment but it has drawback of low water solubility and low permeability. In addition, oral drug delivery to colon faces the problem of gastric degradation and thus increases dose size and frequency. Objectives: The present study was aimed to assay mesalamine and develop an enteric coated mesalamine loaded mucoadhesive beads using guar gum, sodium alginate and carbopol 940 for an effective delivery to colon. Methods: Preformulation study was done to check the purity of drug. The beads were prepared by ion gelation methods and coated with Eudragit S100 and characterized. Results: The melting point and absorbance maxima of mesalamine were found to be 282°C and 220 nm respectively. The FTIR study confirms the drug and polymers were compatible. A total 5 different formulations were prepared which specifically release the drug in the colon region in sustain release fashion. The formulation MA-F4 was chosen as an optimized formulation. The Particle size, Zeta potential, %EE, %Yield, %DL and in vitro drug release of optimized formulation was found to be 445.6 ± 67.1 μm, -28.01 ± 0.16 mV, 94.98 ± 3.22, 96.27 ± 3.22, 30.4 ± 0.9 and 95.07 ± 3.85 respectively. Conclusion: The study demonstrated that the prepared beads can release the mesalamine in sustained release manner and helps in management of IBD.
Keywords: Inflammatory bowel disease; Colon; Mesalamine; Mucoadhesion; Beads